The effect of digital adoption and service quality on business sustainability through strategic alliances at port terminals in Indonesia - Dani Rusli Utama; Mohammad Hamsal; Rano Kartono Rahim; Asnan Furinto (Asian Journal of Shipping and Logistics (AJSL), 2024)
Effective port management is vital for a nation's economic growth. Amid global advancements, ports must ensure business sustainability across social, environmental, and economic domains due to regulations and market demands. Stakeholders often rely on two strategies: digital technology adoption and service quality enhancement. As ports involve diverse stakeholders, collaborative strategies in alliances gain importance. Therefore, this study investigates digital adoption, service quality, and strategic alliances' impact on Indonesian ports' business sustainability. Using quantitative methods, 72 respondents' questionnaire data from Indonesian port terminals was analyzed with structural equation modeling. Results show digital adoption and service quality positively influence strategic alliance formation, which then enhances business sustainability. Interestingly, the direct impacts of digital adoption and service quality on business sustainability are absent, which emphasizes the need for strategic alliances. Thus, Indonesian port terminals should forge alliances as resource-sharing vehicles, promoting business sustainability. This research advances Resource-Based View theory and offers practical insights for navigating Indonesia's port industry challenges while also giving valuable insight about port characteristics in archipelagic countries.
Keywords: 650; Business sustainability; Digital adoption; Service quality; Strategic alliance; Port terminals